PERTANGGUNGJAWABAN PIDANA NOTARIS DALAM MENJALANKAN TUGAS JABATANNYA - , Hendro Wibowo, Harry Purwanto, S.H.,M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the legal protection of the public Notary as evidence in criminal investigation, and to know the procedures for calling Notary or Notary deed performed by the Investigator and how the criminal responsibility of Notary against the deed that is created. This study use empirical juridical approach, which is using legal norms that are explained by way of examining and discussing the criminal responsibility of the Notary in performing their respective duty, and examine how its implementation through field research to obtain primary data. through interviews with informants who have the capacity in this study. From the results and discussion can be obtained the conclusion, that the Notary is not criminally responsible for the accuracy of the deed made by him, but when the deediscontained elements of a criminal fraud committed by a public Notary in the process of making the authentic deed, then the Notary can be prosecuted and subject to criminal sanctions under the Articles off orgery in the book of criminal law. The authentic deed made by a Notary can be categorized into forgery as set forth in the book of criminal law, if the deed made by a Notary is contained one of the following matters falsification of signatures in terms of signing the deed authentic, the contents of the authentic act does not conform to the facts or not in accordance with the truth and it was already known before the Notary, and the authentic deed is made by people who are not entitled or authorized to do so.